The complete mitochondrial genome of Moricella rufonota Rohwer, 1916 (Hymenoptera: Tenthredinidae) and phylogenetic analysis. Issue 8 (3rd August 2021) - Tan, Beibei; Wei, Meicai; Niu, Gengyun
Abstract: We sequenced the complete mitochondrial genome of Moricella rufonota Rohwer, 1916 (Tenthredinidae: Nematinae). The mitogenome is 15, 731 bp in length with an A + T content of 81.9%, 37 typical animal mitochondrial genes, and a 386 bp control region. All the 13 protein-coding genes initiate with a typical ATN and end with TAA. The trnI (+)- trnQ (−)- trnM (+) cluster rearranged as trnM (+)- trnQ (−)- trnI (+) cluster, and the trnW (+)- trnC (−)- trnY (−) cluster rearranged as trnC (+)- trnW (+)- trnY (−) cluster. Phylogenetic analysis confirmed that the Nematinae is the basal lineage of Tenthredinidae, and Moricella rufonota is the basal lineage of Nematinae.